Aging phenomena, probability distribution functions and numerical implementations for Lévy walks. (November 2015) - Deng, K.; Deng, J.; Sun, T.; Guan, Y.; Yang, F.; Sun, H.
Abstract : Lévy walks are non-Markovian stochastic processes, whose explosion of space with time is faster than regular Brownian motion but slower than ballistic motion. More concretely, they correspond to a random walk process with jump distribution, where is a power law waiting-time distribution. In this paper, we first investigate the probability distribution functions of Lévy walks, then discuss their aging phenomena, forward waiting-time probability distribution and numerical implementations.